Long COVID in children and adolescents: COVID-19 follow-up results in third-level pediatric hospital - Jamaica Balderas, Lourdes María del Carmen; Navarro Fernández, Amairani; Dragustinovis Garza, Susana Azeneth; Orellana Jerves, María Isabel; Solís Figueroa, Walter Ernesto; Koretzky, Solange Gabriela; Márquez González, Horacio; Klünder Klünder, Miguel; Espinosa, Juan Garduño; Nieto Zermeño, Jaime; Villa Guillén, Mónica; Rosales Uribe, Rómulo Erick; et al. (Frontiers in Pediatrics, 2023)
Introduction: In children, the manifestations of coronavirus disease 2019 (COVID-19) in the acute phase are considered mild compared with those in adults; however, some children experience a severe disease that requires hospitalization. This study was designed to present the operation and follow-up results of the Post-COVID-19 Detection and Monitoring Sequels Clinic of Hospital Infantil de Mexico Federico Gómez in managing children with a history of SARS-CoV-2 infection. Methods: This was a prospective study conducted from July 2020 to December 2021, which included 215 children aged 0-18 years who tested positive for SARS-CoV-2 on polymerase chain reaction and/or immunoglobulin G test. The follow-up was conducted in the pulmonology medical consultation; ambulatory and hospitalized patients were assessed at 2, 4, 6, and 12 months. Results: The median age of the patients was 9.02 years, and neurological, endocrinological, pulmonary, oncological, and cardiological comorbidities were the most commonly observed among the patients. Moreover, 32.6% of the children had persistent symptoms at 2 months, 9.3% at 4 months, and 2.3% at 6 months, including dyspnea, dry cough, fatigue, and runny nose; the main acute complications were severe pneumonia, coagulopathy, nosocomial infections, acute renal injury, cardiac dysfunction, and pulmonary fibrosis. The more representative sequelae were alopecia, radiculopathy, perniosis, psoriasis, anxiety, and depression. Conclusions: This study showed that children experience persistent symptoms, such as dyspnea, dry cough, fatigue, and runny nose, although to a lesser extent than adults, with significant clinical improvement 6 months after the acute infection. These results indicate the importance of monitoring children with COVID-19 through face-to-face consultations or telemedicine, with the objective of offering multidisciplinary and individualized care to preserve the health and quality of life of these children.